Replication Protein A Presents Canonical Functions and Is Also Involved in the Differentiation Capacity of Trypanosoma cruzi. - Raphael Souza Pavani; Marcelo Santos da Silva; Carlos Alexandre Henrique Fernandes; Flavia Souza Morini; Christiane Bezerra Araujo; Marcos Roberto de Mattos Fontes; Osvaldo Augusto Sant'Anna; Carlos Renato Machado; Maria Isabel Cano; Stenio Perdigão Fragoso; Maria Carolina Elias (PLoS Neglected Tropical Diseases)
Replication Protein A (RPA), the major single stranded DNA binding protein in eukaryotes, is composed of three subunits and is a fundamental player in DNA metabolism, participating in replication, transcription, repair, and the DNA damage response. In human pathogenic trypanosomatids, only limited studies have been performed on RPA-1 from Leishmania. Here, we performed in silico, in vitro and in vivo analysis of Trypanosoma cruzi RPA-1 and RPA-2 subunits. Although computational analysis suggests similarities in DNA binding and Ob-fold structures of RPA from T. cruzi compared with mammalian and fungi RPA, the predicted tridimensional structures of T. cruzi RPA-1 and RPA-2 indicated that these molecules present a more flexible tertiary structure, suggesting that T. cruzi RPA could be involved in additional responses. Here, we demonstrate experimentally that the T. cruzi RPA complex interacts with DNA via RPA-1 and is directly related to canonical functions, such as DNA replication and DNA damage response. Accordingly, a reduction of TcRPA-2 expression by generating heterozygous knockout cells impaired cell growth, slowing down S-phase progression. Moreover, heterozygous knockout cells presented a better efficiency in differentiation from epimastigote to metacyclic trypomastigote forms and metacyclic trypomastigote infection. Taken together, these findings indicate the involvement of TcRPA in the metacyclogenesis process and suggest that a delay in cell cycle progression could be linked with differentiation in T. cruzi.